Characteristics of Travellers from Bosnia and Herzegovina to Africa - Obradovic, Zarema (AVICENA, d.o.o., Sarajevo, 2013)
Conflict of interest: none declared. INTRODUCTION: Travellers from Bosnia and Herzegovina (B&H) travel to different world countries. The awareness of people is changing every day and nowadays travellers seek advices related to their travel and destination more often than before. In the previous years, travellers came to Travel Clinics almost only to get the vaccines which were obligatory for entry into a country. In B&H travel clinics are a part of public health institutes. The largest Travel Clinic which provides service for the highest number of travellers is in the Public Health Institute of Sarajevo Canton, in the city of Sarajevo, which is the capital of B&H. In the last years we have seen an increasing interest for travel to Africa because the highest number of travellers travel to African countries. OBJECTIVE: To show the characteristics of persons travelling to Africa, the reasons of their travel, the destination countries and the types of vaccines applied. MATERIALS AND METHODS: We used protocol books of the Travel Clinic in Public Health Institute of Sarajevo Canton and the data from individual forms of travellers. RESULTS: Persons travelling to Africa make 55% of all travellers that are advised and vaccinated in the Travel Clinic in Public Health Institute of Sarajevo Canton. There are significantly more men than women among people travelling to Africa. The highest number of travellers is in the category of working population which means age group of 20-50 years. The most visited countries are Kenya, Ethiopia, Somalia and Ghana. Travellers received the following vaccines: yellow fever, VHA, VHB, meningitis, tetanus. All travellers were given the advice on how to dress, feed and protect against malaria.